Vampireville - Schreiber, Ellen (Vampire kisses, 2006)
As teen vampire twins Luna and Jagger try to trick a high school soccer star into bonding with Luna for eternity, 16-year-old goth girl Raven Madison and her vampire boyfriend, Alexander, strive to save him.